1999
DOI: 10.1021/la9910529
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay of Lateral and Tiered Interactions in Stratified Self-Organized Molecular Assemblies

Abstract: Hybrid self-assembled monolayers (SAMs) containing well-defined strata of different polarity enable insight into how fundamental interactions lead to higher order structure and may provide useful analogies for self-assembled multilayers, new hybrid materials, and functional biological interfaces. We report amide-containing alkanethiol SAMs with internal polar sublayers that are two amide groups thick and nonpolar overlayers comprising either dodecyl or hexadecyl chains. The assemblies have been characterized b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
92
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(103 citation statements)
references
References 67 publications
8
92
0
1
Order By: Relevance
“…We are thus constrained to use relatively small R groups, where the molecular order of these groups in the SAM is not established, but is almost certainly less than in n-alkanethiolates. [51][52][53][54]77 Whatever the reason, the data in Figures 1 and 2 rates of tunneling. 56 The theory of tunneling through junctions containing SAMs is not sufficiently developed at present to give any guidance to these studies, and it is not clear whether this low sensitivity is expected or not.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…We are thus constrained to use relatively small R groups, where the molecular order of these groups in the SAM is not established, but is almost certainly less than in n-alkanethiolates. [51][52][53][54]77 Whatever the reason, the data in Figures 1 and 2 rates of tunneling. 56 The theory of tunneling through junctions containing SAMs is not sufficiently developed at present to give any guidance to these studies, and it is not clear whether this low sensitivity is expected or not.…”
Section: Figmentioning
confidence: 99%
“…The amide group (-CONH-) is one of the best understood in organic chemistry, 49,50 and while not isostructural with -CH 2 CH 2 -is similar in size, and is known, from prior work, to be compatible with the formation of SAMs. [51][52][53][54][55] ii) Perhaps more importantly, we wished to develop a system of SAMs to use in studies of charge transport that was more easily modified structurally than are derivatives of n-alkanethiolates. Preparing compounds of the structure HS(CH 2 ) n R, where n is 10 -20, and R is a group that we might wish to select, with as few restrictions as possible, from the full range of organic and organometallic groups, can be synthetically arduous.…”
Section: Introductionmentioning
confidence: 99%
“…[9] Some of these include intermolecular hydrogen bonds; [8a,10] electrostatic interactions between dipolar moieties; [11] and control of van der Waals (vdW) interactions between n-alkyl chains. [12] Fort his study,t he vdW-based strategy was employed to change the supramolecular structure of monolayers because it avoids loss of rectification ratio resulting from additional structural modification of HSC 11 BIPY.T he chain length of diluent (HSC n )w as varied while keeping the length of rectifier (HSC 11 BIPY) constant.…”
mentioning
confidence: 99%
“…[30] This particular orientation of the adsorbate molecules might be aided by the amide± amide interactions that are known to help in the lateral stabilization of monolayer structures. [31] After having been exposed to a basic solution of rhenium gluconate for a period of 3 h, the layers of adsorbate 7 were characterized again. CA measurements showed that the surface had become more hydrophilic (h a = 78 ± 3), when compared to the original layer of 7, and an increase in hysteresis (Dh = 49) indicates an increased disorder.…”
Section: Resultsmentioning
confidence: 99%